Epigenetic regulation in intervertebral disc degeneration. Issue 10 (October 2022) - Li, Gaocai; Zhang, Weifeng; Liang, Huaizhen; Yang, Cao
Abstract : Intervertebral disc (IVD) degeneration is the leading cause of low back pain, which has a striking impact on numerous patients. Therefore, comprehensively illuminating the regulatory mechanisms of IVD degeneration is of great significance. Here, we discuss the latest advances in understanding the main epigenetic mechanisms regulating IVD degeneration.